Ultraviolet Emissions from Explosive Detonation Breakout. Issue 3 (March 2022) - Johnson, Stephanie; Schwallier, Joel; Glumac, Nick
Detailed spectroscopic measurements of high explosive detonation breakout in the ultraviolet region are presented. Molecular features associated with CN, NH, OH, and N2 are observed and analyzed. Spectra indicate extreme temperatures well in excess of 5000 K in the first few microseconds after breakout. Molecular bands are found to originate from the detonation products, as opposed to the ambient air, and are strongly attenuated in the presence of oxygen. Implications for forensic analysis of source explosive are discussed. Graphical Abstract